2008
DOI: 10.1111/j.1365-2141.2008.07314.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐genetic insights in paediatric T‐cell acute lymphoblastic leukaemia

Abstract: SummaryPaediatric T-cell acute lymphoblastic leukaemia (T-ALL) is an aggressive malignancy of thymocytes that accounts for about 15% of ALL cases and for which treatment outcome remains inferior compared to B-lineage acute leukaemias. In T-ALL, leukemic transformation of maturating thymocytes is caused by a multistep pathogenesis involving numerous genetic abnormalities that drive normal T-cells into uncontrolled cell growth and clonal expansion. This review provides an overview of the current knowledge on onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
132
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(140 citation statements)
references
References 134 publications
(191 reference statements)
3
132
1
4
Order By: Relevance
“…2,3 Despite the diversity of observed mutations and deletions, transcriptional microarray studies have consistently shown that T-ALL can be classified by five recurrent patterns of gene expression, namely the Immature/LYL1, TAL1, TLX1, TLX3 and HOXA clusters. [4][5][6] The last subgroup is characterized by aberrant activation of the HOXA gene locus on chromosome 7.…”
Section: An Early Thymic Precursor Phenotype Predicts Outcome Exclusimentioning
confidence: 99%
“…2,3 Despite the diversity of observed mutations and deletions, transcriptional microarray studies have consistently shown that T-ALL can be classified by five recurrent patterns of gene expression, namely the Immature/LYL1, TAL1, TLX1, TLX3 and HOXA clusters. [4][5][6] The last subgroup is characterized by aberrant activation of the HOXA gene locus on chromosome 7.…”
Section: An Early Thymic Precursor Phenotype Predicts Outcome Exclusimentioning
confidence: 99%
“…6,7 We therefore proposed that these mutations should be classified as type B aberrations. 2 Type B mutations are prevalent among all T-ALL subtypes and affect a wide variety of cellular processes, including survival and proliferation, cell cycle progression, and epigenetic events. Type B mutations often affect signal transduction pathways, including the NOTCH1, IL7R-JAK-STAT, RAS-MEK-ERK, and PTEN-PI3K-AKT pathways.…”
mentioning
confidence: 99%
“…7 The analyzed genes have been selected based on their involvement in T-ALL pathogenesis as reported by others. 4,[8][9][10][11] Primer sequences are presented in Supplementary Table 1. On the basis of the number of hypermethylated genes patients were divided into CIMP þ and CIMP À groups.…”
Section: Letters To the Editormentioning
confidence: 99%